Antiretroviral Therapy in HTLV-1 Infection: An Updated Overview - Francesca Marino-Merlo; Emanuela Balestrieri; Claudia Matteucci; Antonio Mastino; Sandro Grelli; Beatrice Macchi (Pathogens, 2020)
The human T cell leukemic/lymphotropic virus type 1 (HTLV-1), discovered several years ago, is the causative agent for a rapid progressive haematological malignancy, adult T cell leukemia (ATL), for debilitating neurological diseases and for a number of inflammatory based diseases. Although the heterogeneous features of the diseases caused by HTLV-1, a common topic concerning related therapeutic treatments relies on the use of antiretrovirals. This review will compare the different approaches and opinions in this matter, giving a concise overview of preclinical as well as clinical studies covering all the aspects of antiretrovirals in HTLV-1 infection. Studies will be grouped on the basis of the class of antiretroviral, putting together both pre-clinical and clinical results and generally following a chronological order. Analysis of the existing literature highlights that a number of preclinical studies clearly demonstrate that different classes of antiretrovirals, already utilized as anti-HIV agents, are actually capable to efficiently contrast HTLV-1 infection. Nevertheless, the results of most of the clinical studies are generally discouraging on the same point. In conclusion, the design of new antiretrovirals more specifically focused on HTLV-1 targets, and/or the establishment of early treatments with antiretrovirals could hopefully change the perspectives of diseases caused by HTLV-1.